Effects of photoperiod, salinity and pH on cell growth and lipid content of Pavlova lutheri - Shah, S.M.U. (2014)
The aim of the present work was to study the effects of photoperiod, salinity and pH on growth and lipid content of Pavlova lutheri microalgae for biodiesel production in small-scale and large-scale open-pond tanks. In a 250-mL flask, the cultures grew well under 24 h illumination with maximum specific growth rate, Î¼ max, of 0.12 day-1 and lipid content of 35 as compared to 0.1 day-1 and 15 lipid content in the dark. The salinity was optimum for the cell growth at 30-35 ppt, but the lipid content of 34-36 was higher at 35-40 ppt. Algal growth and lipid accumulation was optimum at pH 8-9. Large-scale cultivation in 5-L and 30-L tanks achieved Î¼ max of 0.13-0.14 day-1 as compared to 0.12 day -1 in small-scale and 300L cultures. Â© 2013 Springer-Verlag Berlin Heidelberg and the University of Milan.